PENGARUH SELF DETERMINATION DAN PEER SUPPORT TERHADAP MOTIVASI BERPRESTASI PADA SANTRI DALAM BIDANG BAHASA ARAB DI PESANTREN PIQ SINGOSARI - Iksan, Mohamad; Wibowo, Mursito Wimbo; Ahya, Awaludin (INCARE, International Journal of Educational Resources, 2022)
The research to determine the effect of Self Determination on Achievement Motivation, Peer Support on Achievement Motivation, Self Determination and Peer Support together on Achievement Motivation. The sample in this research were students aged 13-15 years who took a special class in Arabic with a total of 110 subjects. The data collection technique used Likert scale distribution as a research instrument. The instrument trial was conducted at the Islamic Boarding School Nurul Huda Singosari with N=30. The results showed the effect of Self Determination on Achievement Motivation with an r of 0.510 with a t-test result of 6.157 which is greater than the t table with a significance level of 5%. Peer Support Variable on Achievement Motivation also has an effect of r = 0.439 and t count of 5.083 > t table (1.984). Self Determination and Peer Support variables together also have an influence on Achievement Motivation, with a value of r = 0.597 and F arithmetic (29.55) > F table (3.15). The results of testing the value of the contribution of Relative Self Determination is 57.3%, Peer Support is 42.7% and the total value of the contribution of the two independent variables to achievement motivation is 35.5% while the remaining 64.5% is contributed by other variables that are not discussed in this study.